Effects of mill type (hammer vs roller) and particle size uniformity on growth performance, nutrient digestibility, and stomach morphology in finishing pigs - Wondra, K.J.; Fahrenholz, C.H.; Stark, C.R.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of mill type and particle size uniformity on finishing pigs. In Exp. 1, 120 pigs, with an average initial weight of 105 lb, were fed corn-soybean meal-based diets for 57 d. The corn was milled so that all diets had an average mean particle size of 800 11m (± 20), yet differed in particle size uniformity (Sgw). To obtain the most uniform treatment (1.9 Sgw), corn was milled through a roller mill. The intermediate treatment (2.3 Sgw) was obtained by milling corn through a hammermill. The least uniform treatment (2.7 Sgw) was obtained by blending coarsely and finely ground corn. Growth performance of pigs was not affected by Sgw of the diet. However, digestibilities of DM, N, and GE increased as Sgw was reduced. In Exp. 2, 128 pigs, widl an average initial weight of 150 lb, were fed diets with corn milled to 450 JLm (± 7) in a hammermill or a roller mill. The hammermilled corn had an Sgw of 1.8 and the rollermilled corn had an Sgw of 2.0. The diets were fed in meal or pelleted form. There were no interactions among mill type and diet form. Digestibilities of DM and N were greater for the hammermilled treatments, but no growth performance differences were due to mill type. Pelleting increased ADG 9% and improved efficiency of gain by 5 %. Pelleting also increased the severity of stomach lesions. In conclusion, at 800 and 450 p.m, mill type did not affect growth performance. However, nutrient digestibilities were improved by decreasing variability in particle size, a response that merits further investigation.
Keywords: Swine; Particle size; Pelleting; Roller mill; Performance; Stomach ulcers; G-F